IL-22 suppresses IFN-γ–mediated lung inflammation in asthmatic patients - Pennino, Davide; Bhavsar, Pankaj K.; Effner, Renate; Avitabile, Simona; Venn, Pascal; Quaranta, Maria; Marzaioli, Viviana; Cifuentes, Liliana; Durham, Stephen R.; Cavani, Andrea; Eyerich, Kilian; Chung, Kian Fan; et al. (Journal of allergy and clinical immunology, 2013)
IL-22 controls tissue homeostasis by both proinflammatory and anti-inflammatory effects. However, the anti-inflammatory mechanisms of IL-22 remain poorly investigated. We sought to investigate the anti-inflammatory role for IL-22 in human asthma. T-cell lines derived from lung biopsy specimens of asthmatic patients were characterized by means of flow cytometry. Human bronchial epithelial cells from healthy and asthmatic subjects were stimulated with IL-22, IFN-γ, or the combination of both cytokines. Effects of cytokine stimulation were investigated by using whole-genome analysis, ELISA, and flow cytometry. The functional consequence of cytokine stimulation was evaluated in an in vitro wound repair model and T cell–mediated cytotoxicity experiments. In vivo cytokine expression was measured by using immunohistochemistry and Luminex assays in bronchoalveolar lavage fluid of healthy and asthmatic patients. The current study identifies a tissue-restricted antagonistic interplay of IL-22 and the proinflammatory cytokine IFN-γ. On the one hand, IFN-γ antagonized IL-22–mediated induction of the antimicrobial peptide S100A7 and epithelial cell migration in bronchial epithelial cells. On the other hand, IL-22 decreased epithelial susceptibility to T cell–mediated cytotoxicity by inhibiting the IFN-γ–induced expression of MHC-I, MHC-II, and CD54/intercellular adhesion molecule 1 molecules. Likewise, IL-22 inhibited IFN-γ–induced secretion of the proinflammatory chemokines CCL5/RANTES and CXCL10/interferon-inducible protein 10 in vitro. Consistently, the IL-22 expression in bronchoalveolar lavage fluid of asthmatic patients inversely correlated with the expression of CCL5/RANTES and CXCL10/interferon-inducible protein 10 in vivo. IL-22 might control the extent of IFN-γ–mediated lung inflammation and therefore play a tissue-restricted regulatory role.